IMPLEMENTING CRITICAL LITERACY TO REFRAME NARRATIVE STORIES: A CASE STUDY OF INDONESIAN TERTIARY EFL CLASSROOM - Hanif Nurcholish Adiantika; Emi Emilia; Gin Gin Gustine (University of Kuningan, 2025)
Critical literacy (CL) emphasizes the analysis of texts to understand power dynamics and promote social justice, helping students challenge established norms. However, further research is needed on its integration into the English curriculum for Indonesian university students. This case study explores the strategies used by an EFL teacher to foster CL development among 28 student-teachers at an Indonesian university through narrative texts. Data was gathered through classroom observations, students' reflective journals, and interviews, and thematically analyzed. Findings revealed that the teacher applied strategies such as